The Role of Red Blood Cell Distribution Width in the Severity and Prognosis of Community-Acquired Pneumonia - Qiang Ren; Hebing Liu; Ying Wang; Deyu Dai; Zhennan Tian; Guiwei Jiao; Xiaomin Liu (Canadian Respiratory Journal)
Objectives. The objective of this study is to unravel the correlation between RDW and the severity and prognosis of CAP, as well as exploring RDW with the inflammatory markers white blood cells (WBC), C-reactive protein (CRP), and procalcitonin (PCT). Methods. According to the data characteristics, appropriate statistical methods were selected to analyze the relationship between RDW and the severity and prognosis of CAP patients and to determine whether RDW is associated with the inflammatory markers WBC, CRP, and PCT. Results. The results show that with the increase of PSI and CURB-65 values, the proportion of patients with RDW ≥ 12.987% is significantly higher than that of RDW < 12.987% (P<0.01). When RDW is combined with PSI or CURB-65 to predict the 90-day mortality of CAP patients, the area under the receiver operating characteristic (ROC) curve increased prominently, and if RDW, PSI, and CURB-65 are combined, the area under the ROC curve is maximized. Conclusions. Our findings suggest that the higher RDW value is associated with short-term adverse outcomes in CAP patients. We also find that when RDW, PSI, and CURB-65 are combined, the best performance is achieved to predict CAP 90-day mortality risk.